Let's solve this problem step-by-step.
STEP-BY-STEP EXPLANATION:
We will be using simultaneous equations to solve this problem.
Let's establish the two equations we will be using to solve the problem.
Let present age of father = f
Let present age of son = s
Equation No. 1 -
f = 3s
Equation No. 2 -
f + 15 = 2s
To begin with, we will substitute the value of ( f ) from the first equation into the second equation to solve for ( s ).
Equation No. 2 -
f + 15 = 2s
( 3s ) + 15 = 2s
3s - 2s = - 15
s = - 15
Next we will substitute the value of ( s ) from the second equation into the first equation to solve for ( f ).
Equation No. 1 -
f = 3s
f = 3 ( - 15 )
f = - 45
FINAL ANSWER:
Therefore, the present age of the father is - 45 years old.
It isn't possible for someone to be negative years old but this is the answer that I obtained from the equations.
Hope this helps! :)
Have a lovely day! <3